Determination of Stability Constant and Related Thermodynamics of Complex Formation of Glutamic Acid with Some Rare Earth Metals - KANT CHAUDHARY, RAJESH; KUMAR JHA, RANJEET; KUMAR JHA, AJAY; MOHAN MISHRA, PREM (Asian Journal of Chemistry, 2010)
Practical proton ligand and metal ligand stability constants of the metal ions Y(III), Nd(III) and Pr(III) with glutamic acid ligand at temperature 293 K at constant ionic strength of 0.1 M KNO3 was determined. The stability constant was determined by the method of Bjerrum Calvin pH titration technique as adopted by Irving and Rossotti. The stability constant of metal complexes with glutamic acid shows the sequence Y (III) > Nd(III) > Pr (III). Thermodynamic parameters such as free energy (ΔG), enthalpy charge (ΔH) and entropy charge ΔS have also been calculated.